(untitled) (Raparin Journal of Humanities (RJH), 2020)
The above is the title of this study . The aim of the social diexes is to show its impact on the speech of its members . the social diexes include mam , khal , westa , haji , sheikh …etc in Kurdish. They are a branch of the ragmatic signs which composite of setting : time , place , person , text and social figures . The language of propaganda in election is a kind of language used of praising which electors use to persuade voters . This study attempts to investigate that language in the process of election. Readers expected interesting results , the study shows that 83% of the electors use this language in the posters while 17% of them neglected , do not use this language.